1995
DOI: 10.2136/sssaj1995.03615995005900010030x
|View full text |Cite
|
Sign up to set email alerts
|

Traffic Effects on Water Infiltration in Chisel‐Plow and No‐till Systems

Abstract: Traffic effects on pore structure and hydraulic properties of soils may be affected by site‐specific factors. The objective of this study was to determine if the effects of wheel traffic on infiltration rates in chisel‐plow and no‐till tillage systems differed among five Midwestern locations. Ponded and unsaturated (30‐, 60‐, and 150‐mm water tension head) infiltration rates were measured sequentially using infiltrometers after removing surface residues and the upper 2 cm of soil. Wheel traffic reduced ponded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 0 publications
2
13
0
2
Order By: Relevance
“…This traffic effect is supported by the studies of Ankeny, et al (1995), who reported reductions of up to 95 per cent in infiltration rates resulting from wheel traffic on agricultural soils. The higher bulk density of the cap site would also contribute to increased erosion.…”
Section: Importance Of Surface Managementmentioning
confidence: 63%
“…This traffic effect is supported by the studies of Ankeny, et al (1995), who reported reductions of up to 95 per cent in infiltration rates resulting from wheel traffic on agricultural soils. The higher bulk density of the cap site would also contribute to increased erosion.…”
Section: Importance Of Surface Managementmentioning
confidence: 63%
“…Conversely, on a different study with similar fine‐textured soils, 10 yr after tillage establishment NT reduced INF and increased BD relative to conventional tillage (Lindstrom et al, 1981). Relative to conventional tillage systems, Ankeny et al (1995) showed no difference in INF in sites with less than 7 yr under NT, but INF decreased in NT sites with more than 10 yr since establishment. These results suggest that length of time since establishment of tillage treatments might be an important consideration when evaluating soil physical parameters.…”
mentioning
confidence: 68%
“…The effects of tillage (CP versus NT) on ponded and tension infiltration were measured along with compaction effects (see Section 3.3) at five locations in the Midwestern USA (Ankeny et al, 1995). Ponded infiltration rates were affected significantly by tillage at only two sites.…”
Section: Infiltration Rates and Capacitymentioning
confidence: 99%
“…The work of Freese et al (1993) discussed above (Section 3.1.1) showed the greatest effect of wheel tracks on sprinkle infiltration in chiselplowed areas, where the percentage of applied water infiltrating was reduced from 94% on no-track to 59% on wheel-track positions. Ankeny et al (1990Ankeny et al ( , 1995 studied the effects of wheel tracks on infiltration in CP and NT systems at five locations in the Midwest USA. Both ponded and tension infiltration measurements at three head values were collected (1995).…”
Section: Infiltration Rates and Capacitymentioning
confidence: 99%